Fretting-corrosion in hip implant modular junctions: New experimental set-up and initial outcome. (November 2015) - Royhman, D.; Patel, M.; Runa, M.J.; Jacobs, J.J.; Hallab, N.J.; Wimmer, M.A.; Mathew, M.T.
Abstract: Modern hip prostheses feature a modular implant design with at least one tapered junction. This design can lead to several complications due to the introduction of additional interfaces, which are subjected to various loading conditions and micromotion. The main objective of the current study is to develop a fretting corrosion apparatus, which is able characterise the mechanical and electrochemical behaviour of various existing metal alloy couples during fretting motion. This study describes the design and the main considerations during the development of a novel fretting corrosion apparatus, as well as determination of the machine compliance and the initial testing results. Machine compliance considerations and frictional interactions of the couples are discussed in detail. For the preliminary tests, metal alloy pins, made of Ti6Al4V and wrought high-carbon CoCrMo were mechanically polished to a surface roughness of less than 20 nm. 2 pins (Diameter=11 mm) of either Ti6Al4V or CoCrMo were loaded onto a Ti6Al4V alloy rod at a normal force of 200 N. The interface types included: Ti6Al4V–Ti6Al4V–Ti6Al4V, Ti6Al4V–Ti6Al4V–CoCrMo, and CoCrMo–Ti6Al4V–CoCrMo. The Ti6Al4V rod articulated against the metal alloy pins in a sinusoidal fretting motion with a displacement amplitude of ±50 µm. Bovine calf serum (30 g/L of protein content) was selected as a lubricant and tested at 2 different pH levels (pH 3.0 and 7.6). In all cases, current and friction energy were monitored during the fretting process. The results indicated distinct, material-specific current evolutions and friction energies. No significant differences were observed in electrochemical or mechanical behaviour in response to pH change. In general, Ti6Al4V–Ti6Al4V–Ti6Al4V couples displayed the earliest passivation and superior electrochemical behaviour compared to Ti6Al4V–Ti6Al4V–CoCrMo and CoCrMo–Ti6Al4V–CoCrMo under fretting conditions. In addition, fluctuations in current were observed in specific regions at all instances where Ti6Al4V was coupled with Ti6Al4V. These fluctuations were not observed in instances where Ti6Al4V was coupled with CoCrMo. These findings suggest transitions in the degradation mechanisms at the modular junction as a function of material couples/contacts. The findings may assist in improving the current hip modular junctions. Highlights: Novel fretting-corrosion set-up has been developed for the hip modular junctions. Machine compliance study has been conducted. Three-commonly used metal alloy couples were studied. Machine compliance and frictional interactions played a role in the tribocorrosion process. The findings could assist in improving the hip modular junctions.